Comparison of ultrasonography with computed tomography in the diagnosis of nasal bone fractures - Javadrashid, R (The British Institute of Radiology., 2011)
OBJECTIVES: The aim of this study is to compare ultrasonography with CT in the diagnosis of nasal bone fractures. METHODS: 40 patients (9 female and 31 male) with mid-facial fractures, which were suspected nasal bone fractures, were included. All of the patients had mid-facial CT images. Ultrasonography with a 7.5 MHz transducer (Aloka 3500, Tokyo, Japan) was used to evaluate the nasal bone fractures. All of the sonograms were compared with CT findings for sensitivity, specificity and predictive values. A χ(2) test was applied to the data to assess statistical significance. RESULTS: CT diagnosed nasal bone fractures in 24 of the 40 patients (9 unilateral fractures and 15 bilateral fractures) while ultrasonography diagnosed the fractured bones in 23 patients (9 unilateral fractures and 14 bilateral fractures). Ultrasonography missed one fractured bone in a bilateral fractured case and a unilateral fracture was also missed (two false-negative results). The sensitivity and specificity of ultrasonography in assessing nasal bone fracture in comparison with CT were 94.9% and 100%, respectively. The positive predictive value (PPV) and the negative predictive value (NPV) of ultrasonographic evaluation of the nasal bone fractures were 100% and 95.3%, respectively. The χ(2) test did not show any significant difference between CT and ultrasonography in diagnosis of nasal bone fractures (P = 0.819). CONCLUSION: Ultrasonography can be used as a first line of diagnostic imaging for evaluating nasal bone fractures, especially in children and pregnant women.